Frontal lobe cerebral aneurysm rupture presenting as psychosis. - Hall, D P (1992)
A 23 year old male with acute onset of blunted affect, looseness of associations and auditory hallucinations presented to a tertiary care hospital 10 days after development of symptoms. Before transfer, the patient received a diagnosis of schizophreniform disorder and treatment with haloperidol was started which resulted in moderate improvement. Examination led to detection of a ruptured cerebral aneurysm in the left frontal lobe. Evacuation of the haematoma and repair of the aneurysm resulted in nearly complete resolution of symptoms. The rare incidence of acute aneurysm rupture, presenting in the case described, demonstrates the importance of a complete neurological examination in the evaluation of acute mental status changes.